(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study purposed to determine the government’s supervision of illegal buildings along the river boundaries of Rantepao sub-district, North Toraja regency. This study used qualitative research. The research location was along the river border line of Rantepao sub-district and the Public Works and Public Housing Service. The number of informants in this study was 7 people. The results showed that the direct supervision had been carried out well with the reduction of illegal buildings along the river border, no more traffic jams and the river border area and started to be clean from garbage. Indirect Supervision had been adequate and optimal so that the community who owned the building knew that it controlled so that there was no misunderstanding between the community and the officers, it was hoped that supervision could maintained and further improved, so that no more illegal buildings appear along the river border. Keywords: Government supervision, illegal buildings